Overactive bladder syndrome and bladder wall thickness in patients with obstructive sleep apnea syndrome - Yilmaz,Zahide (2018)
ABSTRACT Objective The main objective of the present study was to evaluate the presence of overactive bladder (OAB) syndrome, nocturia, urgency, and urge incontinence in patients with obstructive sleep apnea syndrome (OSAS), and measure bladder wall thickness (BWT) in these patients. Materials and Methods The patient group was composed of 38 patients with OSAS. The control group was composed of 15 healthy individuals. All patients were evaluated using the Epworth Sleepiness Scale (ESS) and Overactive Bladder Symptom Score (OABSS). The bladder wall thickness was measured by transabdominal ultrasound (US). The presence of nocturia, urinary urgency, and urge incontinence were also evaluated. Results The mean OABSS was significantly higher in the patient group compared with the control group (p=0.048). The minimum oxygen saturation (Min.SO2) of patients with urgency was found to be significantly lower (p=0.014). The time spent below 90% of oxygen saturation (SO2) was significantly longer in patients with urinary urgency (p=0.009). There was no difference in BWT measurements between the patient group and the control group. There was a significant relationship between BWT values and OABSS in patients with OSAS (p=0.002). Conclusion The results of the present study suggest that OSAS is associated with OAB syndrome. As a key symptom of OAB, urgency correlates with hypoxia in cases with OSAS. Although the present study did not observe any difference in BWT measurements between the patients and the control group, there was a correlation between BWT measurements and OABSS in patients with OSAS.